2022
DOI: 10.1007/s00431-022-04405-y
|View full text |Cite
|
Sign up to set email alerts
|

Three-hourly versus two-hourly feeding interval in stable preterm infants: an updated systematic review and meta-analysis of randomized controlled trials

Abstract: Evidence from randomized controlled trials (RCTs) suggests that three-hourly feeding is safe and might help achieve full feeds earlier in preterm infants. We systematically compared the bene ts and harms of three-hourly and two-hourly feeding schedules in preterm infants. We searched electronic databases (MEDLINE, CINAHL, Embase, Web of Science, and Scopus) and trial registries until 30 July 2021 for RCTs comparing the two feeding schedules. We did random-effects meta-analysis using RevMan 5.4 software. The pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Also, the heterogeneity may be related to the different frequencies of olfactory and gustatory stimuli during the intervention and the duration of the intervention. Some studies have shown that three-hour feeds are safe, as longer feeding intervals may improve blood flow and bowel motility after meals and help achieve complete enteral feeding earlier [ 29 ]. However, the studies included in this paper did not have a uniform duration and frequency of interventions, which leads to heterogeneity and thus affects the reliability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the heterogeneity may be related to the different frequencies of olfactory and gustatory stimuli during the intervention and the duration of the intervention. Some studies have shown that three-hour feeds are safe, as longer feeding intervals may improve blood flow and bowel motility after meals and help achieve complete enteral feeding earlier [ 29 ]. However, the studies included in this paper did not have a uniform duration and frequency of interventions, which leads to heterogeneity and thus affects the reliability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…In VLBW infants, systematic reviews and meta-analyses concluded that while using intermittent feeding, 3-hourly versus 2-hourly feeding intervals are comparable, although extremely low-birth-weight (ELBW) infants (birth weight < 1000 g) may reach full enteral feeds earlier when fed twice-hourly 44,45 .…”
Section: Bolus Versus Continuous Feedingmentioning
confidence: 99%
“…In brief, in VLBW infants, continuous and intermittent bolus feeding seem comparable, as are comparable 3-hourly or 2-hourly feeding intervals in intermittent feeding (LOE 3) 4,20 . In infants < 1000 g, a 2-hourly interval may be preferable (LOE 3) 44,45 .…”
Section: Bolus Versus Continuous Feedingmentioning
confidence: 99%
“…Nevertheless, further research is required to determine whether extensively hydrolyzed milk powder can shorten the time of parenteral nutrition and reduce long-term complications. Significant differences exist in the method of nasogastric enteral feeding of preterm infants, especially in the continuous or bolus form and the frequency of feeding ( 5 ). The potential advantages and limitations of each form exist, and further research is required to confirm their advantages and disadvantages.…”
mentioning
confidence: 99%